Islamic Spiritual Guidance for Online Gambling Victims: A Spiritual and Psychological Approach - Apriani; Abd Rahman; Nurlailah; Amir Z Nur; Maswati (CV Edujavare Publishing, 2026)
This study aims to examine the effectiveness of Islamic spiritual guidance for online gambling victims through spiritual and psychological approaches in Makassar City. The phenomenon of online gambling has evolved into a multidimensional social problem, simultaneously damaging the spiritual, psychological, familial, and social dimensions of victims' lives. This study employs a descriptive qualitative approach, involving online gambling addiction victims, Islamic spiritual counselors, and victims' family members as informants. Data were collected through in-depth interviews, participant observation, and documentation, and subsequently analyzed using an interactive analysis model. The findings reveal that the Islamic spiritual approach encompassing the methods of tawbah, muhasabah, tazkiyatun nafs, dhikr, tadabbur of the Qur'an, and the restoration of congregational prayer proved effective in restoring the qalb and ruh dimensions of victims. The psychological approach through behavioral counseling, cognitive restructuring, intrinsic motivation enhancement, Islamic mindfulness, and family counselling complemented the recovery process at the cognitive, emotional, and relational dimensions. The integration of both approaches yielded more comprehensive and sustainable recovery outcomes compared to either approach applied in isolation. The success of the recovery process was influenced by the victims' intrinsic motivation, active family support, a supportive religious environment, and the integrative competence of the counselors.